A comprehensive examination of delayed emotional recovery in borderline personality disorder. (June 2015) - Fitzpatrick, Skye; Kuo, Janice R.
Abstract: Background and objectives: Despite growing attention to emotion processes in borderline personality disorder (BPD), little research has examined delayed emotional recovery (i.e., long-lasting emotions after the termination of an emotionally evocative stimulus) in this population. The extant data on delayed emotional recovery in BPD are limited by a lack of assessment across a range of indices and emotions. The present study addresses these gaps by comparing emotional recovery between individuals with BPD, social anxiety disorder (SAD), and healthy controls (HCs) using a multi-modal assessment approach. Methods: Participants underwent fear, anger, and sadness inductions followed by a 5-min "washout" phase wherein emotional recovery was assessed via self-report, respiratory sinus arrhythmia (RSA), and skin conductance responses (SCR). Results: After controlling for state dissociation, the BPD and SAD group exhibited decreases in RSA, while the HC group showed no changes in RSA after the anger induction only. Groups did not differ in rate of emotional recovery across self-report, RSA, or SCR after fear and sadness inductions. Limitations: The present study is limited by a solely female and small sample, and the short time frame in which emotional recovery was assessed. Conclusions: Findings indicate that individuals with BPD generally do not exhibit delayed emotional recovery, but may show decreases in parasympathetic activity during the recovery period after experiencing anger. However, this pattern may not be specific to this disorder. Highlights: We examined emotional recovery of fear, anger, and sadness among individuals with BPD, SAD, and HCs. BPD and SAD groups show decreases in parasympathetic activity across the recovery period after the anger induction. Rate of emotional recovery after fear and sadness inductions is similar across groups. Individuals with BPD generally do not show delayed emotional recovery. Delayed emotional recovery in BPD may be index and emotion specific.